(untitled) (Acta Scientiarum. Biological Sciences, 2026)
The body condition factor in fish is widely used as a tool to detect variations in individual fitness associated with habitat quality and food availability. In August 2019, one of the most significant environmental disasters in the history of tropical oceans impacted the Brazilian coastline, affecting multiple ecosystems and fishing communities. In this context, the present study aimed to assess the impact of the disaster on 14 fish species by analyzing interannual variations from 2014 to 2020. We tested the hypothesis that the 2019 oil spill significantly affected the condition factor (K). The study was conducted along the northern coast of Pernambuco state, in northeastern Brazil, using fixed arrowhead-type traps for fish sampling. K estimates for the 14 fish species revealed apparent interannual variability. Notably, all species exhibited variations during or after the 2019 oil spill, particularly in 2020, when K values fell below 1, indicating poor body condition. The most pronounced effects were observed in Archosargus rhomboidalis, Caranx bartholomaei, Chaetodipterus faber, Diapterus auratus, Haemulon parra, Haemulon plumieri, Haemulopsis corvinaeformis, Lutjanus analis, and Opisthonema oglinum. These structural changes in the fish assemblage suggest the presence of sublethal effects from oil exposure, capable of compromising physiological integrity even in the absence of direct mortality. This study highlights the value of biometric indicators, such as the K factor, as sensitive tools for the early detection of environmental disturbances.